2017
DOI: 10.1103/physreve.96.062210
|View full text |Cite
|
Sign up to set email alerts
|

Mobility-induced persistent chimera states

Abstract: We study the dynamics of mobile, locally coupled identical oscillators in the presence of coupling delays. We find different kinds of chimera states, in which coherent in-phase and anti-phase domains coexist with incoherent domains. These chimera states are dynamic and can persist for long times for intermediate mobility values. We discuss the mechanisms leading to the formation of these chimera states in different mobility regimes. This finding could be relevant for natural and technological systems composed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…1(a)]. In the vicinity of these regions, persistent chimera states may form, where ordered and disordered domains coexist [45]. We exclude time-delay values within these regions to avoid the presence of persistent chimera states which affect synchronization dynamics, as has been shown elsewhere [45].…”
Section: Mobile Coupled Oscillators With Delayed Couplingmentioning
confidence: 99%
See 3 more Smart Citations
“…1(a)]. In the vicinity of these regions, persistent chimera states may form, where ordered and disordered domains coexist [45]. We exclude time-delay values within these regions to avoid the presence of persistent chimera states which affect synchronization dynamics, as has been shown elsewhere [45].…”
Section: Mobile Coupled Oscillators With Delayed Couplingmentioning
confidence: 99%
“…In the vicinity of these regions, persistent chimera states may form, where ordered and disordered domains coexist [45]. We exclude time-delay values within these regions to avoid the presence of persistent chimera states which affect synchronization dynamics, as has been shown elsewhere [45]. Furthermore, here we fix the value of κ = 0.1 and consider delay values within the first and second stable branches of solutions to avoid in-phase multistability [15,16].…”
Section: Mobile Coupled Oscillators With Delayed Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that synchronization time may depend non-monotonically on the mobility of oscillators and the mechanism of driving synchronization are different for different dynamical regimes [43][44][45]. Chimera dynamics in mobile oscillators has not been investigated except for a recent work, in which an array of locally coupled oscillators exchange positions and the persistent chimera states may be maintained under the interplay between the mobility and time delay [46].…”
Section: Introductionmentioning
confidence: 99%